PELATIHAN STARTING MOTOR Y/D MENGGUNAKAN PLC PENGAJAR TEKNIK OTOMASI INDUSTRI SMK MUHAMMADIYAH 1 KEPANJEN - Tresna Umar Syamsuri; Abdul Manaf; Harrij Mukti K; Ruwah Joto; Sigi Syah Wibowo (UPT Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Malang, 2020)
PLC training aimed at instructors of the Industrial Automation Engineering Skills Competency Program in Muhammadiyah 1 Kepanjen, can improve the skills and motivation of teachers and students to know and understand PLCs and improve skills in making/assembling PLC practice modules for the development of PLC practice subjects. In addition, it can also increase additional skills for PLC field teachers in accordance with the applicable curriculum in SMK Muhammadiyah 1 Kepanjen.